Zn penetration and its coupled interaction with the grain boundary during the resistance spot welding of the QP980 steel. (September 2022) - Dong, Wufeng; Pan, Hua; Lei, Ming; Ding, Kai; Gao, Yulai
Abstract: The liquid metal embrittlement (LME) defect in the Zn-coated high-strength steels is intimately associated with the formation of Fe-Zn intermetallic compounds (IMCs). The relationship between LME crack propagation and Fe-Zn IMCs during the resistance spot welding of the galvanized QP980 steel was systematically investigated. The results showed that LME cracks were mainly generated in the center of the weld (type I crack) and the shoulders of the weld (type II crack) for the galvanized QP980 resistance spot welded joint. The longest type Ⅰ crack was around 1014.8 and 95.7 μm for type Ⅱ crack. Moreover, the details of the microstructure and element distribution near the LME crack were analyzed. The brittle Fe-Zn IMCs were traced at the grain boundaries to initiate the cracks. In addition, these brittle IMCs could further weaken the grain boundaries of the steel substrate and resultantly promote the formation and further propagation of LME cracks. Graphical abstract: Image, graphical abstract